Association between self-reported sleep disorders and prevalence of chronic kidney disease in a nationally representative sample of U.S. adults - Xiao, Hua; Liu, Kai; Hong, Guobao; Zhang, Xinzhou (Frontiers in Psychiatry, 2025)
BackgroundChronic kidney disease (CKD) is associated with various health complications, including sleep disorders. Understanding the relationship between CKD and sleep disturbances is essential for improving patient management and outcomes in this population.Patients and methodsThis study analyzed data from the National Health and Nutrition Examination Survey (NHANES) across two cycles (2015–2016 and 2017-2018), involving 4758 participants aged 20 years and older. Sleep disorders were evaluated via targeted questions from the Sleep Disorders Questionnaire. Chronic kidney disease (CKD) was classified by low estimated glomerular filtration rate (eGFR) and proteinuria. Logistic regression analyses examined the association between sleep disorders and CKD, adjusting for demographic and lifestyle confounders.ResultsAmong 4,758 participants, 863 (14%) were diagnosed with chronic kidney disease (CKD). Elevated C-reactive protein (CRP) levels and differential leukocyte counts were observed in the CKD cohort. CKD was associated with increased reports of snoring, sleep apnea, and sleep disturbances, along with higher fatigue levels. A significant positive association between CKD and sleep difficulties persisted in adjusted models. Infrequent snoring (1–2 times per week) demonstrated a negative association, whereas excessive daytime sleepiness (16–30 times/month) correlated positively with CKD. Significant associations between sleep disorders and CKD were observed in participants aged <60, with a BMI <28 kg/m², normal blood pressure, and CRP ≥1.8 mg/L. Sleep disorders were found to be correlated with obesity, hypertension, diabetes, CKD, and proteinuria. Notably, CKD patients with sleep difficulties had markedly elevated CRP levels compared to those without sleep issues, while other inflammatory markers were similarly elevated (P < 0.001).ConclusionPatients with chronic kidney disease experience higher rates of sleep issues, highlighting the importance of addressing these problems in CKD management.